2014
DOI: 10.1007/s10689-014-9736-1
|View full text |Cite
|
Sign up to set email alerts
|

Germline CDKN2A mutations in Brazilian patients of hereditary cutaneous melanoma

Abstract: Approximately 10 % of all cutaneous melanoma cases occur in a familial context. The major susceptibility gene for familial melanoma is CDKN2A. In Latin America, genetic studies investigating melanoma predisposition are scarce. The aim of this work was to investigate germline CDKN2A point mutations and genomic rearrangements in a cohort of 59 Brazilian melanoma-prone patients. Screening of CDKN2A alterations was performed by sequencing and multiplex ligation probe amplification. Germline CDKN2A mutations affect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 28 publications
1
24
1
Order By: Relevance
“…Partial genetic information of the patients with melanoma from Spain and Brazil, and a subset of pedigrees from Uruguay, has been previously reported. 16 , 17 , 18 , 19 , 20 , 21 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Partial genetic information of the patients with melanoma from Spain and Brazil, and a subset of pedigrees from Uruguay, has been previously reported. 16 , 17 , 18 , 19 , 20 , 21 …”
Section: Methodsmentioning
confidence: 99%
“…Few studies have assessed the prevalence of CDKN2A mutations or MC1R variants and phenotypic characteristics in patients at high risk for melanoma from Latin American countries. CDKN2A mutations have been identified in 13.6% of melanoma-prone families from São Paulo, Brazil, 16 whereas one study reported no mutations in Porto Alegre, 17 and in a different cohort the mutation frequency was 7%. 18 In melanoma-prone families from Uruguay, 5/6 families had CDKN2A mutations.…”
Section: Introductionmentioning
confidence: 98%
“…The patients were classified into three groups: hereditary melanoma carrying pathogenic CDKN2A -mutations ( n = 8), familial history of melanoma without CDKN2A -mutations ( n = 20), and sporadic cases (without family history of the disease; n = 41). The 20 hereditary melanoma patients who had previously tested negative for CDKN2A -mutations [ 27 ] fulfilled at least one of the following criteria: (a) familial melanoma (family history of three or more relatives of two consecutive generations with melanomas, at least one case before 50 years old; n = 9) or (b) multiple primary melanomas (≥3 primary lesions, n = 8; or ≥2 primary melanomas, one of which before 35 years old, n = 3).…”
Section: Methodsmentioning
confidence: 99%
“…[8] A number of studies have reported difficulties in collecting reliable data for many communicable diseases, compromising its epidemiological monitoring. [9][10][11][12] The lack of widespread EHRs and interoperability gaps between systems contribute on delays and on disseminating errors. [9] To be able to rely additionally on other systems can help support epidemiological monitoring.…”
Section: National Unified Public Health System (Sus) Including the Bmentioning
confidence: 99%